SENTIMENT ANALYSIS OF COMMENTS ON TOURIST ATTRACTIONS IN LAMPUNG PROVINCE USING THE NAIVE BAYES METHOD - Wirahudha, Muhammad Arif; Damayanti, Damayanti; Megawaty, Dyah Ayu (Informatika, Universitas Jenderal Soedirman, 2025)
Lampung Province is a province that has so much natural beauty, this also makes Lampung Province one of the tourist destinations that are visited by many domestic and foreign tourists so that there is a problem, namely the many negative comments that are not in accordance with reality affect the number of tourist visits to Lampung Province because they are not in accordance with reality so that they affect public opinion about tourism in Lampung Province which results in tourist attractions being deserted. The method used to analyze sentiment analysis is the naive bayes algorithm by crawling data using python. The stages of the naive bayes algorithm in the study using preprocessing consist of five processes, namely cleansing, tokenization, case folding, stopword removal, and stemming. Lampung Province tourist attractions are Pahawang, Way Kambas, Krui Beach / West Coast, Mutun Beach and Kiluan Bay. The results of a fairly high level of accuracy in positive comments on Pahawang Beach. In this study, it was concluded that the impact of comments can affect the number of visitors coming to tourist attractions.